2020
DOI: 10.1002/eji.201948428
|View full text |Cite
|
Sign up to set email alerts
|

Global miRNA and mRNA expression profiles identify miRNA‐26a‐2‐3p‐dependent repression of IFN signature in systemic sclerosis human monocytes

Abstract: Dysregulation in type I IFN and IFN-stimulated genes (ISGs) induced by monocytes is one of the key features of systemic sclerosis (SSc) pathogenesis. Abnormalities in microRNA (miRNA) expression are related to excessive IFN production, however the role of miRNA remains largely elusive in SSc monocytes. This study explores global miRNA-mRNA profiling of SSc monocytes and functional attenuation of IFN and ISGs by specific miR-NAs. Global sequencing of mRNA (mRNA-seq) and miRNA (miRNA-seq) samples were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…In addition, ROC analysis revealed that enhanced expression of circulating miRNA-146b in sera and synovial fluids was a better disease activity biomarker than the CRP level. Similarly, miRNA-mRNA co-sequencing and functional analysis identified miRNA-26a as a new candidate which is predicted to negatively regulate IFN-regulated genes in systemic sclerosis (SSc) monocytes [54]. This implies that reduced expression of miRNA-26a may be involved in the pathogenic IFN signature in SSc monocytes.…”
Section: Role Of Mirnamentioning
confidence: 97%
“…In addition, ROC analysis revealed that enhanced expression of circulating miRNA-146b in sera and synovial fluids was a better disease activity biomarker than the CRP level. Similarly, miRNA-mRNA co-sequencing and functional analysis identified miRNA-26a as a new candidate which is predicted to negatively regulate IFN-regulated genes in systemic sclerosis (SSc) monocytes [54]. This implies that reduced expression of miRNA-26a may be involved in the pathogenic IFN signature in SSc monocytes.…”
Section: Role Of Mirnamentioning
confidence: 97%
“…Transfection of miR-26a-2-3p mimics to TLR-stimulated THP-1 cells proved that this miRNA is a negative regulator of IFN-stimulated genes. These findings suggest that miR-26a-2-3p downregulation might be responsible, at least in part, for the increased IFN production in SSc [91].…”
Section: Immune Dysfunction and Mirnasmentioning
confidence: 81%
“…The comparison of transcriptomes between monocytes from healthy controls and monoctyes from patients with SSc revealed a dysregulation in the inflammatory pathways, including the pathway for IFN signaling (Figure 1A and Supplementary Figure 8A, available on the Arthritis & Rheumatology website at http://onlinelibrary.wiley.com/doi/10.1002/art.41737/abstract). Previous studies demonstrated that the type I IFN signature was up‐regulated in the peripheral blood of patients with SSc (23–25). Similarly, in our cohort, elevated serum levels of IFNα2 were observed (Supplementary Figure 8B [http://onlinelibrary.wiley.com/doi/10.1002/art.41737/abstract]).…”
Section: Resultsmentioning
confidence: 99%